A bridge over the Balkans - Arapoglou, Eleftheria. (Piscataway, NJ)
x, 186 sayfa
Keywords: “This critical study of Demetra Vaka Brown, one of the most significant Greek American writers of the turn of the last century, is framed within the fields of “Orientalism” and cultural studies. At once a white female and a Greek immigrant from the Ottoman Empire, she worked as a writer in the United States, publishing in English and contributing her work to mainstream publications. The book presents the identity politics of Vaka Brown, recovering the discursive techniques in her identification processes and assessing the significance of her agency in the context of the themes and preoccupations of Orientalism“ -- Yayıncı.